Endosonographic features predictive of benign and malignant gastrointestinal stromal cell tumours. Issue 1 (1st January 2000) - Palazzo, L; Landi, B; Cellier, C; Cuillerier, E; Roseau, G; Barbier, J-P
Abstract : BACKGROUND/AIM: Some endoscopic ultrasonographic (EUS) features have been reported to be suggestive of malignancy in gastrointestinal stromal cell tumours (SCTs). The aim of this study was to assess the predictive value of these features for malignancy. METHODS: A total of 56 histologically proven cases of SCT studied by EUS between 1989 and 1996 were reviewed. There were 42 gastric tumours, 12 oesophageal tumours, and two rectal tumours. The tumours were divided into two groups: ( a ) benign SCT, comprising benign leiomyoma (n = 34); ( b ) malignant or borderline SCT (n = 22), comprising leiomyosarcoma (n = 9), leiomyoblastoma (n = 9), and leiomyoma of uncertain malignant potential (n = 4). The main EUS features recorded were tumour size, ulceration, echo pattern, cystic spaces, extraluminal margins, and lymph nodes with a malignant pattern. The two groups were compared by univariate and multivariate analysis. RESULTS: Irregular extraluminal margins, cystic spaces, and lymph nodes with a malignant pattern were most predictive of malignant or borderline SCT. Pairwise combinations of the three features had a specificity and positive predictive value of 100% for malignant or borderline SCT, but a sensitivity of only 23%. The presence of at least one of these three criteria had 91% sensitivity, 88% specificity, and 83% predictive positive value. In multivariate analysis, cystic spaces and irregular margins were the only two features independently predictive of malignant potential. The features most predictive of benign SCTs were regular margins, tumour size ⩽30 mm, and a homogeneous echo pattern. When the three features were combined, histology confirmed a benign SCT in all cases. CONCLUSIONS: The combined presence of two out of three EUS features (irregular extraluminal margins, cystic spaces, and lymph nodes with a malignant pattern) had a positive predictive value of 100% for malignant or borderline gastrointestinal SCT. Tumours less than 30 mm in diameter with regular margins and a homogeneous echo pattern are usually benign.